Immunogenicity of 60 novel latency-related antigens of Mycobacterium tuberculosis - Serra-Vidal, Mᵃdel Mar; Latorre, Irene; Franken, Kees L. C. M.; Díaz, Jéssica; de Souza-Galvão, Maria Luiza; Casas, Irma; Maldonado, José; Milà, Cèlia; Solsona, Jordi; Jimenez-Fuentes, M. Ángeles; Altet, Neus; Lacoma, Alícia; et al. (Frontiers in Microbiology, 2014)
The aim of our work here was to evaluate the immunogenicity of 60 mycobacterial antigens, some of which have not been previously assessed, notably a novel series of in vivo-expressed M.tuberculosis (IVE-TB) antigens. We enrolled 505 subjects and separated them in individuals with and without latent tuberculosis infection (LTBI) versus patients with active tuberculosis. Following an overnight and 7 day stimulation of whole blood with purified recombinant M.tb antigens, interferon-γ (IFN-γ) levels were determined by ELISA. Several antigens could statistically significantly differentiate the groups of individuals. We obtained promising antigens from all studied antigen groups (DosR regulon encoded antigens; resuscitation-promoting factors (Rpf) antigens; IVE-TB antigens; reactivation asociated antigens). Rv1733, which is a probable conserved transmembrane protein encoded in DosR regulon, turned out to be very immunogenic and able to discriminate between the three defined TB status, thus considered a candidate biomarker. Rv2389 and Rv2435n, belonging to Rpf family and IVE-TB group of antigens, respectively, also stood out as LTBI biomarkers. Although more studies are needed to support our findings, the combined use of these antigens would be an interesting approach to tuberculosis immunodiagnosis candidates.